Enantiotropic inconstancy, crystalline solid solutions and co-crystal in the salicylic acid–anthranilic acid system. Issue 43 (28th October 2022) - Nordstrom, Fredrik L; Mohajerani, Seyed Sepehr; Linehan, Brian; Ricci, Francesco
Abstract : T–X phase diagram of salicylic acid–anthranilic acid with three crystalline solid solution phases and a co-crystal, resulting in variable enantiotropic transition temperature and a polymorphic co-existence domain. Abstract : The phase boundaries and thermodynamic properties of crystal phases in the salicylic acid (SA) – anthranilic acid (AA) system have been determined experimentally. The complete binary T–X diagram reveals a total of four crystalline phases, including a co-crystal and three crystalline solid solutions. The two eutectics were determined through triplicate DSC analyses at 33 compositions. By adding a liquid solvent and generating a ternary phase diagram, a methodology is introduced to determine the solid-state miscibility limits of the solid solutions at 20 and 55 °C. The crystalline solid solutions exhibit substantial differences in physical properties relative to the pure components, including solubility enhancements that are relevant for chemical processing and material properties. The thermodynamic relationships of the three polymorphs of AA have been resolved showing an enantiotropic transition temperature of 50–55 °C between Form I and III of pure AA. However, as a result of the solid solutions with SA, the enantiotropic transition temperature was suppressed by around 30 °C at the eutectoid. In addition, a co-existence envelope is formed, wherein the two AA polymorph solid solutions exist in equilibrium with one another over a wide range of temperatures and compositions.